Early management of pediatric pulmonary tuberculosis with iron deficiency anemia: a case report - Hartadi, Putu A.; Suryaningsih, Putu S. (International Journal of Advances in Medicine, 2025)
Tuberculosis (TB) in children is often difficult to diagnose due to nonspecific symptoms and limited microbiological testing. Severe anemia in children is usually evaluated for nutritional deficiencies or hematological disorders, but can also be an indicator of chronic infections such as TB. In this case, a child with severe anemia without typical respiratory symptoms was finally diagnosed with TB after further evaluation. This case report emphasizes the importance of high suspicion of TB in unclear anemia, as well as the role of transfusion in stabilization and diagnosis. A 4-year-old girl was referred to Wangaya with moderate hypochromic microcytic anemia, suspected iron deficiency anemia (IDA). The patient had fever, cough, and runny nose since 23 November 2024, accompanied by a decrease in haemoglobin (Hb) to 6.7 g/dl. Peripheral blood examination showed hypochromic microcytic with poikilocytosis, suggesting IDA or possibly thalassemia. Nutritional status was good, but there was underweight and short stature. The patient was admitted for further evaluation. In this case, continued evaluation of the unimproved anemia led to the diagnosis of tuberculosis, despite the absence of prominent respiratory symptoms. This emphasizes the importance of considering TB as a differential diagnosis in children with anemia of unclear etiology. Blood transfusion can play an important role in clinical stabilization while supporting the diagnosis and management process.